Let´s take this verified equation:

**(a + b) x ( a – b) = a2 – ab + ba -b2**

**-ab** and **+ba** cancel each others, which gives us:

**(a + b) x (a – b) = a2 – b2**

*Now we divide both terms by ***( a – b), **which gives us:

**(a + b) x (a – b) / a – b = a2 – b2 / a – b**

*The left part can be reduced to:*

**(a + b) = a2 – b2 / a – b**

*Now we assign the values, ***a = b = 1**, it gives us:

**1 + 1 = 1 – 1 / 1- 1**

*So the equation becomes ***1 + 1 = 1** ( When you divide a number by it´s equal it always gives 1 ) The equation then gives us:

**2 = 1**

By adding **1** to each side it gives us **3 = 2** or

**3 = 1 + 1**

*Source: Bernard Weber, Encyclopedia of relative and absolut knowledge.*

This equation has been applied in physical terms during my life experience,

2 = 1 or 1 + 1 = 3,

I had the very exact same result, she´s called *Nashira* 1 Soul + 1 Soul created another one, or in a different perspective, 2 Persons create 1 out of love and passion, 2 = 1 is confirmed aswell.

### Like this:

Like Loading...

*Related*